FEATURES OF ATTITUDES TO THE HEALTH OF YOUNG PEOPLE WITH DIFFERENT LEVELS OF PSYCHO-EMOTIONAL STRESS - Batsylyeva, Olha; Puz, Irina; Hresko, Inna (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to the topical problem of attitude to the health and state of psycho-emotional stress. In particular, the article considers the concept of attitude to health, which is a system of individual, selective connections of the individual with various phenomena of the surrounding reality, contributing to or, conversely, threatening the health of people, and determining the assessment of the individual’s physical and mental state, as well as the criteria of adequate/inadequate attitude to health (cognitive, emotional, behavioral and value-motivational criteria) and the factors determining the process of its formation, for example: age, level of education, specific culture, the dominant locus of control and others. A review of the concept of psycho-emotional stress is also carried out, which is characterized by a different degree of mobilization of neuropsychological functions of the body and can manifest itself at three levels: minor manifestations of signs of tension, activation of psycho-emotional reactions and disruption of functional systems. And since there is a correlation between a person’s emotional state and his or her ability to assume responsibility for and take care of his or her own health, in particular, with growing anxiety and dissatisfaction with life, there is a tendency to shift from the internal to the external control of health, for example a high level of psycho-emotional stress can cause an inadequate attitude to health. Accordingly, was the stating experiment to test assumptions that there are differences in relation to the health of young people with different levels of emotional stress, including young people with a high level of emotional stress is characterised by an inadequate attitude to health. So an inadequate attitude to health is manifested in low level of competence in the area of health, the lack of action for the strengthening and preservation of health, lack of understanding of the importance its in human life, and also in the presence of indifference to him and his secondary importance in the hierarchy of values of the individual. As a result of the experiment, we have seen that young people with low levels of psycho-emotional stress is characterized by an adequate attitude to health at all four levels, exactly: cognitive, emotional, behavioral and value-motivational, which can not be said about the people with a high level of psycho-emotional stress. Young people with a high level of psycho-emotional stress are characterized by an unconscious attitude to health, ignorance of the factors that positively or negatively affect health, misunderstanding of its importance for the efficiency of human activity and in ensuring longevity, as well as the behavior of such respondents does not meet the conditions of a healthy lifestyle, and at the emotional level they have an inadequate level of anxiety for health, or, conversely, show complete indifference, therefore, they do not attach high importance to health in the individual hierarchy of values and have insufficient motivation to strengthen and preserve it.